Pengaruh Profesionalisme Dan Kompetensi Auditor Internal Terhadap Kemampuan Mendeteksi Kecurangan (Fraud) Pada Bank Muamalat Di Palembang - Febrian Wicaksana; Hilda Hilda; Rachmania Rachmania (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The research aims to determine the effect of professionalism and competence on the ability to detect fraud. This research was carried out at Bank Muamalat KC Palembang. This type of research is quantitative research with a sample method using a saturated sample method and data collection using a survey method with questionnaires as a data collection technique. The samples used were 30 samples. The test tool uses SPSS Version 26. The analysis method in this research uses the multiple regression analysis method. The results of this research show that professionalism does not influence the ability to detect fraud and competence influences the ability to detect fraud.